Integração de informação e interoperabilidade: o Repositório Institucional como suporte à gestão da investigação na Universidade de Aveiro - Martins, Ana Bela (2013)
The information management strategy of University of Aveiro provides a set of systems interoperable with each other and with other external systems, to allow process simplification, the promotion of appropriate information management and the research visibility. The Institutional Repository of the University of Aveiro (RIA) is a centerpiece in this area and, during the development of the system, the team had identified a set of key features to make agile the process of deposit of publications and to allow integration with other systems. Some of these features are described and highlighted the challenges.